Effective IT governance mechanisms in higher education institutions: An empirical study - Bianchi, Isaías Scalabrin (2020)
Particular attention to IT Governance is required when the pervasive use of technology has created critical dependencies on IT for organizational performance and prosperity. This study attempts to assess the importance of specific mechanisms for the effectiveness of IT governance in the context of higher educational institutions. Using a qualitative approach with in-depth interviews and document analysis to collect data, a study was carried out across several countries. A mechanism in each type (structure, process, and relational) emerge as quite important: IT Strategy Committee (structure), IT Strategic Planning (process) and IT Leadership (relational).